Oral History: The “Unspoken” and the Importance of Hearing Those Who Have Been Silenced (Global Journal of Human-Social Science, 2023)
This article intends to understand the meanings and representations of silences A demonstration of the importance of giving voice to those who have been silenced by state imposition fear or shame will be discussed Listening to those who have always been silenced enables them to build a new story or a story with otherness Words are not always extracted from those who do not or cannot speak In this case being silenced brings as well as says clear messages Consequently the interpretation of these silences is fundamental
Keywords: words silences give voice